Impact of Different Household Cooking Methods on the Nutritional Composition, Total Phenolic Content and Invitro Antioxidant Activities of African nightshade (Solanum scabrum) and Vegetable amaranth (Amaranthus hybridis) - Njong, Clementine Endam; Manga, Gilbert Ghislain Mbassi; Sonchieu , Jean; Ejoh , Richard Aba (Journal of Food Sciences, 2025)
Purpose: The objective of this study was to subject African nightshade and vegetable Amaranth to different household cooking methods (boiling, steaming, microwave and stir frying) and test them on the changes of total phenolic content (TPC), antioxidant property (ferric reducing-antioxidant power (FRAP) activity and DPPH radical scavenging activity), macronutrients and micronutrients. Methodology: The African nightshade, (HB) and the Amaranthus leaves, (AL) used in the preparation of all the dishes were purchased from the same farmer at Nkwen in Mezam division of the North West Region of Cameroon. Standard methods were used to determine each analyte at the Laboratory of Food Science and Metabolism (LabSAM) of the University of Yaounde 1 and Nkolbisson Food Technology Laboratory, Yaounde, Cameroon. Findings: The TPC of leafy vegetables ranged from 256.64 to 1184.08 mg GAE/100g, with higher levels observed in cooked forms compared to raw ones. Steaming significantly increased FRAP in both African nightshade and amaranth, followed by microwaving and boiling, with steamed samples showing the highest antioxidant activity. Cooking methods also enhanced DPPH free radical scavenging activity, with microwaved African nightshade (HBM) and steamed amaranth (ALS) exhibiting the highest activity. Nutritional analysis revealed variations in dry matter, ash, protein, crude fiber, and total sugars, with steamed vegetables (ALS, HBM, HBS) generally having higher nutrient levels. Mineral and vitamin analyses showed iron (19.08–34.87 mg/100g DW), zinc (1.06–3.92 mg/100g DW), vitamin C (93.85–231.42 mg/100g DW), and provitamin A (16.5–62.85 mg/100g DW) levels were higher in cooked vegetables compared to their raw counterparts. Unique contribution to theory, practice and policy: This study demonstrates that different cooking techniques impact the nutritional composition and antioxidant activities of the indigenous vegetables; African nightshade and vegetable amaranth. The findings provide valuable insights for optimizing the cooking methods of these vegetables to enhance their health benefits. Thus this study greatly contributes to providing healthy choices on the different ways in which these vegetables can be cooked.